Pengaruh ZIS (Zakat Infak dan Shadaqah) Produktif Terhadap Peningkatan Pendapatan Para Mustahik (Studi Kasus di BMT Mekar Da’wah dan Baznas Jakarta Tahun 2005) - Husnul Khatimah (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2005)
Management and distribution of zakah, infaq and shadaqah (ZIS) are the fundamental problem in the Islamic economics. At the first time, zakah just collected and distributed with the target to fulfill primary need of mustahik only. Currently the innovative management of zakah through productive financing to mustahik are -the specific phenomena in Islamic economics. This research tend to find the impact of zakah in order to increase income of mustahik that the object of zakah distribution through productive financing and to deeply understanding about how to couching and counseling program by BMT Mekar Da’wah. The results of wilcoxon signed rank shown that the most of "mitrabmaan" (mustahik) gets significant increasing of their income after distribution of zakah. And the result of regression shown that the contribution ofzakah to increasing income of mustahik are not significant The other variables may influence of increase the income example: the economic conditions, motivation to develop of mustahik, the couching and counseling method, etc.